2023
DOI: 10.3390/w15213866
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic from Wastewater Using Hydrochar Prepared from Red Macroalgae: Investigating Its Adsorption Efficiency and Mechanism

Aisha Khan Khanzada,
Muhammad Rizwan,
Hussein E. Al-Hazmi
et al.

Abstract: Arsenic (As) is a prominent carcinogen component produced via both geogenic and anthropogenic processes, posing serious risks to human health. This study aimed to investigate the potential of hydrochar prepared from red macroalgae for removing As from synthetic wastewater. The hydrochar was produced through 5 h hydrothermal carbonization (HTC) treatment at 200 °C, and then, chemically activated with ferric chloride hexahydrate (FeCl3·6H2O). SEM analysis revealed a permeable structure of hydrochar, while FTIR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 94 publications
0
0
0
Order By: Relevance
“…When more biochar is added to the solution, the number of active sites also increases, providing more opportunities for arsenic to be adsorbed onto the biochar (Nguyen et al 2019). These results are consistent with the findings of (Khanzada et al 2023).…”
Section: -2 Effect Of Adsorbent Dosagesupporting
confidence: 93%
See 3 more Smart Citations
“…When more biochar is added to the solution, the number of active sites also increases, providing more opportunities for arsenic to be adsorbed onto the biochar (Nguyen et al 2019). These results are consistent with the findings of (Khanzada et al 2023).…”
Section: -2 Effect Of Adsorbent Dosagesupporting
confidence: 93%
“…Fig 3 . illustrates that the arsenic adsorption efficiency improved from 60% to 88% with the increasing of pH from 2 to 6 and decreased from 88% to 66% with the increasing of pH from 6 to 10. This trend of increasing adsorption efficiency at pH 6 was consistent with previous investigations carried out by (Poo et al 2018;Khanzada et al 2023), who also found that the optimal pH for arsenic removal was around 6-8, and the most efficient removal occurred at pH 6. Additionally, the current investigation revealed that the binding of metal ions is influenced by the pH levels and the surface groups present on the adsorbent (Rahmani and Amini 2016).…”
Section: -1 Effect Of Phsupporting
confidence: 91%
See 2 more Smart Citations
“…Sebastian et al [48] have reported that heavy metals like Cd and As can be effectively absorbed and immobilised by Fe3O4. However, in the absence of surface modification with stabilising agents like starch or carboxymethyl cellulose, Fe3O4 particles tend to agglomerate and trapped among soil particles [49]. Overall, this application aligns with Sustainable Development Goal 15: Life on Land, which emphasizes the need to protect, restore, and promote sustainable use of terrestrial ecosystems, including addressing land degradation and combating desertification.…”
Section: Immobilizationmentioning
confidence: 76%